Analisis Kualitas Jaringan Internet di Perpustakaan UINSU sebagai Sumber Informasi bagi Pengguna - Yusniah Yusniah; Iyen Supit; Adha Rahimi (Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
The existence of the internet in the library is an interesting thing that must be put to good use by students to improve the quality of their services. This new phenomenon will change the service principles that have been adhered to by libraries, namely enriching collections and increasing number of users to come to the library. Searching for information via the internet is very useful for information seekers, because they can browse information relatively quickly and precisely. This research uses a type of qualitative research that requires as much information and data as possible to achieve research objectives. This type of research is a case study because this research is carried out in depth with an institution and with a narrow subject. As a case study, the data collected comes from various sources of literature. This research results that the quality of the internet network in the UINSU Library has an important role in the student learning process. Especially students who don't have their own laptops, they can do their assignments at the UINSU Library. It is also very important when they do group assignments, they can use the space provided to do their group assignments. Keywords: Information Search, Library, Internet Network